The humble Stonechat Saxicola rubicola and the species neglected by ornithological research in Italy (Avocetta, 2024)
The query of one of the major online scientific research databases returned quite worrying data, because a large group of species breeding in Italy, 47 out of 270 (17%) has never been studied and this number grows further (56 species, 20.7% of the total) if we consider that 9 species with published papers have 0 h-index (i.e. do not yet have any citations). These species neglected by Italian ornithological research have been called ‘zero species’. Bird species without indexed studies are 87.2% native and mostly migratory (66.0%). They live mainly in wetlands (36.2%) and forest habitats (27.7%) and generally have an increasing population trend (44.7%). Furthermore, the majority of these species are classified as least concern by the Italian Red List (44.7%), with a lower percentage of threatened species (34.0%). Zero species are more unprotected than protected ones (61.7% vs 38.3%). Finally, 42.6% of them belong to passerines and have a very restricted geographical range (83.0%). Some examples of zero species are reported and discussed, such as the Stonechat Saxicola rubicola, the Common redpoll Acanthis flammea or the Red Kite Milvus milvus, highlighting some of their interesting traits that could stimulate research aimed at conservation.
Keywords: Italian ornithology; bird database; zero species; web research